Educação Ambiental Crítico-Transformadora via temas geradores e Sociedades Sustentáveis: uma análise das concepções de sustentabilidade dos licenciandos da UFSCar Sorocaba - Costa, Larissa Carvalho Miragaia (Universidade Federal de São Carlos, 2023)
Environmental degradation has reached exorbitant levels in recent years. Thus, Environmental Education (EE) emerged, aiming to circumvent the environmental crisis that has taken place worldwide, through awareness, which consists of a naïve view of concrete reality. This way of understanding the environment does not consider social, economic, and political issues articulated with the current model of social organization. Thus, the critical view of the world goes beyond the conservation and preservation of the environment, considering the correlation between human beings-nature-society, excessive consumption and the generation of waste driven by capitalism. The UFSCar Sorocaba (SP) Campus was built based on the principle of sustainability and points to this issue as transversal in its institutional development proposal. In view of this, this research arose from the perspective of identifying the vision of undergraduate students in the last year of the undergraduate courses of this university, in relation to sustainability articulated with Environmental Education. Thus, from the political-pedagogical Macrotrend of Critical Environmental Education, the foundations of Critical-Transformative Environmental Education via Generating Themes (EACT-TG), based on Freirean, can be articulated to the conception of Sustainable Societies. In this context, we end up using sustainability views that can be classified as Naive or Critical for data analysis. Most of the answers were characterized as naïve views in relation to environmental issues/sustainability/Environmental Education. Therefore, we suggest that UFSCar Campus Sorocaba can consider more teaching-learning moments of Critical Environmental Education, especially through the articulation between the fundamentals of EACT-TG and Sustainable Societies, for the training of future environmental educators, adjusting their curricular matrices to this perspective of EE.
Critical-Transformative Environmental Education via Generating Themes and Sustainable Societies: an analysis of the conceptions of sustainability of UFSCar Sorocaba undergraduates
Keywords: Formação Inicial de Professores; Degradação Ambiental; Macrotendências de Educação Ambiental; Paulo Freire; Initial Teacher Training; Ambiental Degradation; Environmental Education Macro Trends; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO